Sedimentary anatomy and hydrological record of relic fluvial deposits in a karst cave conduit. Issue 1 (13th September 2020) - Bella, Pavel; Gradziński, Michał; Hercman, Helena; Leszczyński, Stanisław; Nemec, Wojciech
Abstract: This case study from the renowned Demänová Cave System in the Carpathians of Slovakia demonstrates that the conventional methods of fluvial sedimentology, combined with an allostratigraphic mapping and speleothem U‐series isotopic dating, can give unprecedented insights into the hydrological history of underground karst conduit. The deposits studied are a relic compound sidebar ranging from gravel to mud and encapsulating the conduit's hydrological history from the middle Pleistocene to the present time. A succession of 10 allostratigraphic units, time‐constrained by speleothems, are recognized in the sidebar deposits, and the corresponding morphodynamics of an evolving cave‐floor sedimentation are reconstructed in considerable detail. The subterranean river water stages recognized from the deposits, time‐constrained by flowstone layers and stalagmites, correlate with and add to the regional record of climate changes. Two distinct episodes of flow ponding (high‐stage slackwater conditions) are recognized and attributed to the independently documented downstream cave‐roof collapses, probably triggered by the Carpathian post‐orogenic earthquakes. This multidisciplinary study may serve as a useful methodological guide for the analysis of fluviokarstic deposits in speleological research and reconstruction of their hosting cave hydrological history.